2021
DOI: 10.1186/s12884-021-04288-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress and coping among unmarried pregnant university students in South Africa

Abstract: Background The improvement of maternal and child health (MCH) outcomes is an important part of the sustainable development goals (SDGs). MCH remains an important issue globally as the SDGs have not yet been achieved in most countries. Young women in universities are likely to experience unintended pregnancy due to risky sexual behaviors in tertiary institutions which is characterized by lack of condom and/or contraceptive use and coercion. Pregnant young women in an academic environment are sus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
2
0
2
Order By: Relevance
“…In one previous study, it was reported that material needs to be a main reason for such pregnancy followed by coercion or abuse (13). Furthermore, one previous study conducted in South Africa identified that academic demand during university education is considered a reason for unmarried pregnancy (14).…”
Section: Items Frequency Percentmentioning
confidence: 99%
“…In one previous study, it was reported that material needs to be a main reason for such pregnancy followed by coercion or abuse (13). Furthermore, one previous study conducted in South Africa identified that academic demand during university education is considered a reason for unmarried pregnancy (14).…”
Section: Items Frequency Percentmentioning
confidence: 99%
“…According to Phiri and al, from South Africa, " In universities, young women can experience an undesired pregnancy as a result of risky sexual behavior in their academic environment marked by the lack of utilization of condoms and/or contraceptives and duress" [11].…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos 10 años el incremento de mujeres que son o se convierten en madres durante los estudios universitarios, ha llamado la atención de investigadores de diferentes disciplinas para develar el desacoplamiento de los roles normativos al ser madres y estudiantes universitarias (Miller & Arvizu, 2016;Reina-Barreto et al, 2019); los significados que representa la experiencia de la maternidad para estudiantes universitarias (Lucchini-Raies et al, 2018); las condiciones socioeconómica y afectivas de jóvenes madres y sus familias (González-Bedoya & Molina-Osorio, 2018); las alteraciones del ciclo de vida y las afectaciones económicas y de salud mental que implica la maternidad en etapa universitaria (Hernández et al, 2020;Hernández-Quirama et al, 2019); así como las estrategias para compatibilizar las actividades académicas y familiares de jóvenes madres universitarias (Álvarez et al, 2020); el estrés ocasionado por embarazos y maternidades no deseadas durante los estudios universitarios (Phiri et al, 2021); la percepción de los efectos de la maternidad en el ámbito laboral, académico y social (Herrera, 2021); incluso, durante la pandemia, reconocer las oportunidades que trajo la educación universitaria a distancia para el ejercicio de la maternidad de las jóvenes estudiantes (Burk et al, 2021;Cárdenas-Ramos & Chalarca-Carmona, 2022;Sánchez & Valdéz, 2021).…”
Section: Introductionunclassified